Modeling and process simulation of vibration assisted workpiece in micro-EDM using FEM. (13th June 2016) - Maity, Kalipada; Choubey, Mayank
Abstract : Purpose: Micro-electro discharge machining (EDM) plays an important role in the fabrication of micro holes in an electrically conductive high-strength material. The flushing of debris poses a great challenge in the micro-EDM operation. The vibration of workpiece plays a significant role in the flushing of debris of the workpiece. Design/methodology/approach: This study aims that the finite element analysis is performed using ANSYS software to find out the maximum displacement of the workpiece at a different location at different frequencies. For the convergence of this analysis, the natural frequency obtained from ANSYS is validated with some available literature. Findings: The continuous up and down vibration of the workpiece results in the formation of vapor bubbles in a low-pressure region that contributes to material removal due to the fracture of bubbles. The vibration-assisted workpiece in the micro-EDM process causes the pressure variation of dielectric between the electrode and workpiece that enhances material removal rate because of cavitation. Originality/value: In workpiece vibration-assisted micro-EDM, the selection of correct vibration frequency and displacement is of greater importance because improper frequency selection can cause bending of the wire electrode, affecting machining stability and short circuiting.